Rezeption und Reform im japanischen und deutschen Recht - Zweites Rechtswissenschaftliches Symposion Göttingen - Kansai, Göttingen, September 2006 - Jehle, Jörg-Martin; Lipp, Volker; Yamanaka, Keiichi (Universitätsverlag Göttingen, 2008)
Basis of the volume is the Second Law Symposium Göttingen - Kansai on reception and reform in the German and Japanese law, which was held in September 2006 with significant participation of colleagues from the Kansai University, Osaka, and the Georg-August-Universität Göttingen.